Solve the system by substitution. y = 3x – 2 y = 4x

Question

Solve the system by substitution.
y = 3x – 2
y = 4x

in progress 0
Lệ Thu 23 hours 2021-07-21T23:58:50+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-07-22T00:00:33+00:00

    Answer:

    x = -2

    y = -8

    Step-by-step explanation:

    y = 3x – 2

    y = 4x

    Substituting the second equation for y into the first

    4x = 3x – 2

    Subtract 3x from both sides

    x = -2

    plug in x = -2 into the second equation

    y = 4(-2)

    y = -8

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )